2004
DOI: 10.1021/nl049550b
|View full text |Cite
|
Sign up to set email alerts
|

Straightening Suspended Single Walled Carbon Nanotubes by Ion Irradiation

Abstract: Single walled carbon nanotubes grown suspended between pillars of Si/SiO 2 structures are straightened by ion beam scans. In addition, the ion irradiation selectively removes nanotubes lying on the substrate, leaving the suspended nanotubes in place. This strategy provides a facile way to produce large area connected networks of suspended straight nanotubes. Although ion irradiation induces structural modifications to nanotubes and introduces defects into the nanotube lattice, the form and dimensions of the na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 15 publications
0
28
0
Order By: Relevance
“…This has been demonstrated in the Fe-oxide nanoparticle system. [47] The impact of ions on nanostructured objects will be influenced by object size, [36] shape (due to angle of impact effects), [48,49] as well as other physical characteristic effects such as how the objects are supported [51] or if they are porous. [50] The two latter characteristics may lead to environmental effects as objects suspended in space respond differently to an ion beam than when they are supported on a substrate, and a porous structure may adsorb and retain ambient gases or solvents for considerable time in vacuum.…”
Section: Probe Effectsmentioning
confidence: 99%
“…This has been demonstrated in the Fe-oxide nanoparticle system. [47] The impact of ions on nanostructured objects will be influenced by object size, [36] shape (due to angle of impact effects), [48,49] as well as other physical characteristic effects such as how the objects are supported [51] or if they are porous. [50] The two latter characteristics may lead to environmental effects as objects suspended in space respond differently to an ion beam than when they are supported on a substrate, and a porous structure may adsorb and retain ambient gases or solvents for considerable time in vacuum.…”
Section: Probe Effectsmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16] Besides, it was demonstrated that nanotubes can be interconnected or merged 9,12,17,18 and that irradiation can give rise to many interesting phenomena, such as extreme pressure inside nanotubes 19 or fullerenelike "onions," 6,20 so that these systems can be used as nanolaboratories for studying pressure-induced transformations at the nanoscale. Furthermore, recent experiments indicate that ion, [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] electron, 6,39-52 and high energy photon [53][54][55][56] irradiation can be used to tailor the mechanical, 8,10 electronic, 11,[21][22][23] and even magnetic …”
Section: Introductionmentioning
confidence: 99%
“…The initial efforts involved applying FIB to modify and manipulate CNTs directly with Ga+ ion beams [13][14][15][16]. However, due to the high impact momentum of Ga + , the carbon atoms are easily knocked out from their lattice locations and structural defects were induced inside the CNTs.…”
Section: Introductionmentioning
confidence: 99%